Mixed Neuroendocrine-Non-neuroendocrine Neoplasm (MiNEN) of the Esophagus: A Case Report - Cristina G, Domingo; Gerardo H, Cornelio (Asian Pacific Journal of Cancer Care, 2022)
Esophageal cancer incidence rates have been increasing over the past years and survival rates remain low. According to the Global Cancer Observatory, 3.1% of new cancer cases consists of esophageal cancer and 5.5% of deaths was due to esophageal cancer. Histologic classification comprises of either squamous cell carcinoma (SCC) or Adenocarcinoma. Other types are reported to be uncommon. We present a case of 33-year old male admitted due to progressive dysphagia. He underwent esophagogastric resection and histopathologic studies revealed a mixed neuroendocrine- non-neuroendocrine tumor. He received adjuvant chemotherapy. On mid-cycle evaluation, the patient showed no evidence of disease recurrence.